Correlation between anemia during delivery and developmental delay - Bajalan, zahra; Amir Ali Akbari, sedigheh; Soleimani, farin; Alavi Majd, hamid (Advances in Nursing & Midwifery, 2013)
Abstract Introduction: Because of the necessity for more and different follow-ups in children with developmental disorders in the early years of lifetime, determination of effective factors during pregnancy is important in any society. This study was performed to reveal a correlation of anemia in mothers during childbirth with developmental status of 12-month infants. Materials and Methods: This study was performed through designing descriptive correlation on 250 mothers and their 12-month infants who visited to health services centers affiliated to Qazvin University of Medical Sciences and Health-Treatment Services in 1390 in multistage sampling method. Data collection tool included informational forms, Ages and Stages Questionnaire, as well as infant anthropometric measurements were taken by the researcher with the meter and scale. Thereafter, the data was statistically analyzed with Software SPSS16 and Chi-square, Independent T, Mann-Whitney and Logistic regression tests. Results: The results showed that the average age of mothers in developmental delay group was 28.39±5.17and in natural developmental group was 27.68±5.15. The most frequency of mothers had primary school education and homemaker. 66.7% out of all infants in anemic group and 55% in non-anemic group are boys. Prevalence of iron-deficiency anemia in the studied society was 12% and prevalence of developmental delay of children was 22.4%. Anemia had a significant correlation with developmental status of infants and its communicational domain (p<0.05). In the logistics model, hemoglobin showed significant correlation with developmental status of infants (p=0.02 and OR=0.31). Also the male gender had a value close to significance level (p=0.55 and OR=0.052). Other variables had no correlations. Conclusion: There is probability that occurrence of infants’ developmental delay is as a result of anemia because iron is necessary for development of central nervous system. Keywords: Anemia, Ages and Stage Questionnaire, Developmental dela